مفهوم الاجتهاد وحتميته عند وحيد الدين خان - سعود,ابراهيم; بوسجادة,أحمد (University of Eloued جامعة الوادي, 2023)
الاجتهاد في الإسلام هو الدليل القويّ على قابلية وصلاحية أحكام الشريعة الإسلامية لمواجهة جميع التحدّيات والأحداث والوقائع المستجدّة، وهو دليل كذلك على شمول الإسلام وصلاحيته لكلّ زمان ومكان. ولقد أرسى الإسلام أصولا ومبادئ وكلّيات تضبط حركة الاجتهاد لتلبية جميع الحاجيات، ولقد بيّن العلماء الأصوليون أحكام الاجتهاد وفصّلوا فيها ودعوا إليه. وفي العصر الحديث زادت الحاجة إلى الاجتهاد نظرا للتغيّر الهائل الذي شمل جميع مناحي الحياة، حيث عرف عدّة نوازل ووقائع احتيج فيها إلى اجتهادات جديدة، ولقد دعا العلماء المعاصرون إلى ضرورة الاجتهاد في مثل هذه الوقائع، ومن هؤلاء المفكّر الهندي وحيد الدين خان. تتناول هذه الدراسة مفهوم الاجتهاد ( تعريفه وشروطه وأحكامه )، وتقف على تأكيد وحيد الدين خان على أهمية الاجتهاد وضرورته في العصر الحديث، مع تسليط الضوء على مجالات ومواضيع وجب مراجعتها وإعادة الاجتهاد فيها . Abstract: Search in Islam is the strong evidence of the viability and validity of the rules of Islamic law to face all challenges, events and emerging realities, and it is also evidence of the comprehensiveness of Islam and its validity for every time and place. Islam established fundamentals, principles, and colleges that organise the movement of search to achieve all requirements, and fundamentalist scholars have clarified the rulings of search, elaborated on them, and did it. In the modern era, the need for search increased due to the tremendous change that included all aspects of life, as it witnessed several calamities and incidents in which new search was needed. Contemporary scholars must seek for the necessity of search on such facts, such as the Indian scientist Wahiduddin Khan. This study deals with the concept of search (definition, terms and conditions), and the study stands on Wahiduddin Khan's emphasis on the importance of search and its necessity in the modern era, while highlighting areas and topics that must be reviewed and re-search in it, following to the renewable human needs.
Keywords: وحيد الدين خان; التجديد; search Islamic rules; Wahiduddin Khan; renewal; needs